High-toughness, insulating and heat-conducting PC composite material and preparation method thereof
Through the melting composite of modified high-purity alumina and silicone modified polycarbonate, combined with the surface treatment of long-chain silane coupling agent, the contradiction between thermal conductivity and toughness of insulating thermal conductivity is solved, and efficient thermal conduction and impact resistance is achieved. Performance, suitable for high-end electronic and electrical appliance fields.
Patent Information
- Application Number
- CN202411111261.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-14
- Publication Date
- 2024-12-27
AI Technical Summary
Existing insulating thermal conductivity materials are difficult to take into account both thermal conductivity, toughness and flame retardant properties. Especially in the field of thermally conductive polycarbonate, the performance is easily damaged after filling with a large amount of thermally conductive filler, which cannot meet the needs of high temperature and mechanical stress.
通过将改性高纯氧化铝与有机硅改性聚碳酸酯和其他助剂经熔融复合,形成特定配比的高韧绝缘导热PC复合材料,结合长链硅烷偶联剂进行表面处理和高温煅烧,形成牢固的化学键以优化无机填料与有机基体的界面相容性。
It achieves efficient heat conduction and impact strength, maintains the high insulation properties of polycarbonate, extends the service life of the material, and is suitable for high-end electronics and electrical fields.
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of polymer material modification, and in particular to a high-toughness insulating and thermally conductive PC composite material and a preparation method thereof. Background Art
[0002] With the improvement of electronic equipment integration, the reduction of component volume and weight, and the increase of transmission speed and power of electronic components, the heat concentration inside the equipment also increases accordingly, which affects the accuracy and service life of the equipment. In order to ensure the reliable operation of functional devices, effective thermal management materials are essential. Therefore, higher requirements are placed on the thermal conductivity and mechanical properties of polymer materials. The development of functional plastics with excellent mechanical properties, flame retardant properties and thermal conductivity has extremely important economic and practical value.
[0003] Common insulating thermal conductive materials are difficult to balance thermal conductivity, toughness and flame retardancy. Polycarbonate has good flame retardancy, high strength, elastic modulus, high impact strength, good fatigue resistance, good dimensional stability, small creep (very little change under high temperature conditions), high transparency and free dyeing, and has been widely used in electrical, electronic, automotive and other industries. The defects of polycarbonate are strong rigidity and difficulty in bending, high glass transition temperature, high viscosity, insufficient hydrolysis stability, and sensitivity to notches. At present, it is mainly through the compounding of ABS with polycarbonate, and the use of silicone and polycarbonate copolymerization for modification, glass fiber filling, to improve the toughness of polycarbonate, but it is limited to conventional use. In the field of thermal conductive polycarbonate, a large amount of thermal conductive fillers are filled, and its performance is easily damaged, especially the notch impact reduction is very obvious, making it unusable in many devices that require heat dissipation.
[0004] In order to overcome the above problems, through continuous research and improvement of the material preparation process and performance, this patent modifies the thermal conductive filling powder alumina and polycarbonate to prepare a thermal conductive polycarbonate material with good thermal conductivity, insulation, flame retardancy and high temperature resistance.
[0005] Therefore, how to provide a high-toughness, insulating and thermally conductive PC composite material and a preparation method thereof is a problem that technical personnel in this field urgently need to solve. Summary of the invention
[0006] One object of the present invention is to provide a high-toughness insulating thermally conductive PC composite material and a preparation method thereof. The polycarbonate modified material prepared by the present invention has high toughness, good thermal conductivity, insulation, flame retardancy and high temperature resistance; a specific proportion of modified high-purity alumina in the composite material is combined with a variety of thermally conductive fillers, which not only achieves efficient thermal conductivity, but also maintains the original high insulation properties of polycarbonate, meeting the special requirements of the electronic and electrical fields for materials; enhances the impact strength and toughness of the composite material, and ensures reliability and durability under high temperature or mechanical stress; forms a strong chemical bond on the surface of alumina, optimizes the interface compatibility between the inorganic filler and the organic matrix, and also improves the thermal stability in the polycarbonate modification, extending the service life of the material.
[0007] A high-toughness insulating and thermally conductive PC composite material according to an embodiment of the present invention is formed by melt-compounding modified high-purity alumina, silicone-modified polycarbonate and other additives;
[0008] The composite material is prepared by melting and compounding the modified high-purity alumina at a ratio of 25%, the organic silicon modified polycarbonate at a ratio of 65% and other additives at a ratio of 10%.
[0009] Furthermore, the aluminum oxide can be angular aluminum, quasi-spherical aluminum, flaky aluminum oxide, or aluminum oxide whiskers, and the size of the aluminum oxide is 20-40000 nm.
[0010] Furthermore, the other additives are composed of toughening agent, thermal conductive filler, coupling agent, antioxidant and flame retardant, and the ratio of the other additives is: toughening agent 12%, thermal conductive filler 60%, coupling agent 2%, antioxidant 1% and flame retardant 25%.
[0011] Furthermore, the thermally conductive filler is a mixture of at least two thermally conductive materials.
[0012] Furthermore, the method for preparing the composite material comprises the following steps:
[0013] Step 1: High-purity alumina is repeatedly washed with water to a purity of more than 99.9%;
[0014] Step 2: using a long-chain silane coupling agent for surface treatment and performing two high-temperature calcination treatments;
[0015] Step 3: silicone-modified polycarbonate: a long-chain silane coupling agent is selected and mixed with polycarbonate powder at high speed, and after the surface of the polycarbonate is completely wetted, heat treatment is performed at 120° C. for 2 hours to obtain a long-chain silane-modified polycarbonate;
[0016] Step 4: Mix the treated modified high-purity alumina, silicone-modified polycarbonate and other additives, and then perform high-temperature melt granulation to obtain a high-toughness insulating and thermally conductive polycarbonate composite material.
[0017] Furthermore, the number of carbon atoms in the alkyl chain is ≥8.
[0018] Further, the aluminum oxide modification method comprises the following steps:
[0019] Step 1: Alumina is repeatedly washed with deionized water until the purity of the alumina is ≥ 99.9%;
[0020] Step 2: Dry at 120 degrees for 2 hours, then heat to 800 degrees, calcine for 2 hours, and finally slowly heat to 1500 degrees and keep the temperature constant for 2 hours;
[0021] Step 3: dilute the long-chain silane coupling agent in ethanol, and add 1000g of alumina to 100g of the long-chain silane coupling agent;
[0022] Step 4: wet stirring for half an hour, and then drying at 150°C for 4 hours.
[0023] Furthermore, the coupling agent is diluted in ethanol at a mass ratio of 1:4.
[0024] Furthermore, the fluidity of the polycarbonate is 1-30 g / 10 min.
[0025] The beneficial effects of the present invention are:
[0026] The polycarbonate modified material prepared by the present invention has high toughness, good thermal conductivity, insulation, flame retardancy and high temperature resistance; a specific proportion of modified high-purity alumina in the composite material is combined with a variety of thermal conductive fillers, which not only realizes efficient thermal conductivity, but also maintains the original high insulation properties of polycarbonate, meeting the special requirements of the electronic and electrical fields for materials; the impact strength and toughness of the composite material are enhanced, and the reliability and durability under high temperature or mechanical stress are guaranteed; a strong chemical bond is formed on the surface of alumina, the interface compatibility between the inorganic filler and the organic matrix is optimized, and the thermal stability is also improved in the polycarbonate modification, thereby extending the service life of the material. DETAILED DESCRIPTION
[0027] With the improvement of electronic equipment integration, the reduction of component volume and weight, and the increase of electronic component transmission speed and power, the heat concentration inside the equipment also increases accordingly, which affects the accuracy and service life of the equipment. In order to ensure the reliable operation of functional devices, effective thermal management materials are essential. Therefore, higher requirements are placed on the thermal conductivity and mechanical properties of polymer materials. The development of functional plastics with excellent mechanical properties, flame retardant properties and thermal conductivity has extremely important economic and practical value.
[0028] Common insulating thermal conductive materials are difficult to balance thermal conductivity, toughness and flame retardancy; polycarbonate has good flame retardancy, high strength, elastic modulus, high impact strength, good fatigue resistance, good dimensional stability, small creep (very little change under high temperature conditions), high transparency and free dyeing, and has been widely used in electrical, electronic, automotive and other industries; polycarbonate defects are strong rigidity and difficulty in bending, high glass transition temperature, high viscosity, insufficient hydrolysis stability, and sensitivity to notches. At present, it is mainly through the compounding of ABS and polycarbonate, and the use of silicone and polycarbonate copolymerization for modification, glass fiber filling, to improve the toughness of polycarbonate, but it is limited to conventional use. In the field of thermal conductive polycarbonate, filling a large amount of thermal conductive fillers, its performance is easily damaged, especially the notch impact reduction is very obvious, making it unusable in many devices that require heat dissipation.
[0029] In order to solve the above problems, the following technical solutions are proposed:
[0030] The invention provides a high-toughness insulating and thermally conductive PC composite material, which is formed by melting and compounding modified high-purity alumina, organosilicon modified polycarbonate and other additives; the composite material has a ratio of 25% of modified high-purity alumina, 65% of organosilicon modified polycarbonate and 10% of other additives.
[0031] Specifically, the aluminum oxide can be angular aluminum oxide, quasi-spherical aluminum oxide, flaky aluminum oxide, or aluminum oxide whiskers, and the size of the aluminum oxide is 20-40000 nm.
[0032] Other additives are composed of toughening agent, thermal conductive filler, coupling agent, antioxidant and flame retardant. The ratio of other additives is: 12% toughening agent, 60% thermal conductive filler, 2% coupling agent, 1% antioxidant and 25% flame retardant; the thermal conductive filler is a mixture of at least two thermal conductive materials.
[0033] The specific proportion of modified high-purity alumina (25%) in the composite material is combined with a variety of thermally conductive fillers, which not only achieves efficient thermal conductivity, but also maintains the original high insulation properties of polycarbonate (65%), meeting the special needs of the electronic and electrical fields for materials.
[0034] More specifically, the method for preparing the composite material comprises the following steps:
[0035] Step 1: High-purity alumina is repeatedly washed with water to a purity of more than 99.9%;
[0036] Step 2: using a long-chain silane coupling agent for surface treatment and performing two high-temperature calcination treatments;
[0037] Step 3: silicone-modified polycarbonate: a long-chain silane coupling agent is selected and mixed with polycarbonate powder at high speed to completely wet the surface of the polycarbonate, and heat-treated at 120° C. for 2 h to obtain a long-chain silane-modified polycarbonate;
[0038] Step 4: Mix the treated modified high-purity alumina, silicone-modified polycarbonate and other additives, and then perform high-temperature melt granulation to obtain a high-toughness insulating and thermally conductive polycarbonate composite material.
[0039] In the steps of the composite material preparation method, step one is to ensure that the aluminum oxide has extremely high purity, which is crucial for obtaining high-performance composite materials, especially for applications with strict requirements on electrical insulation and thermal conductivity; step two is that the coupling agent can effectively improve the interface compatibility between the aluminum oxide particles and the organic matrix (such as polycarbonate), the first calcination helps the coupling agent molecules to be better coated on the aluminum oxide surface, and the second calcination further solidifies the coupling layer to form a stronger chemical bond, thereby enhancing the overall performance of the composite material; step three is through this step, the silane coupling agent reacts chemically with the polycarbonate matrix to form a modified polycarbonate Acid esters enhance the toughness, heat resistance and compatibility of the matrix with other materials, laying the foundation for the subsequent preparation of composite materials; Step four is to obtain a high-toughness insulating and thermally conductive polycarbonate composite material through this series of operations. This composite material not only maintains the original good insulation of polycarbonate, but also significantly improves the thermal conductivity of the material by adding high-purity alumina. At the same time, the addition of other additives further enhances the comprehensive properties of the material, such as toughness, heat resistance, flame retardancy, etc., making it suitable for the production of high-end electronic packaging materials, LED heat dissipation components, and structural parts under complex working conditions that require high insulation, high thermal conductivity and high toughness.
[0040] More specifically, the alumina is repeatedly washed with deionized water until the purity of the alumina is ≥99.9%, then dried at 120 degrees for 2 hours, heated to 800 degrees C, calcined for 2 hours, and finally slowly heated to 1500 degrees C and kept at a constant temperature for 2 hours. The long-chain silane coupling agent is diluted in a mixed solution of ethanol and water (the mass ratio of coupling agent: ethanol: water is 10:70:20), 1000g of alumina is added to 100g thereof, wet-stirred for half an hour, and then dried at 150 degrees C for 4 hours, and the moisture content is reduced to ≤0.03%.
[0041] Long-chain silane coupling agent, the number of alkyl chain carbons ≥8.
[0042] Alumina modification method, alumina modification method steps:
[0043] Step 1: Alumina is repeatedly washed with deionized water until the purity of the alumina is ≥ 99.9%;
[0044] Step 2: Dry at 120 degrees for 2 hours, then heat to 800 degrees, calcine for 2 hours, and finally slowly heat to 1500 degrees and keep the temperature constant for 2 hours;
[0045] Step 3: dilute the long-chain silane coupling agent in ethanol, and add 1000g of alumina to 100g of the long-chain silane coupling agent;
[0046] Step 4: wet stirring for half an hour, and then drying at 150°C for 4 hours.
[0047] The invention discloses a method for preparing polycarbonate modified by a long-chain organic silicon coupling agent. The coupling agent is diluted in ethanol at a mass ratio of 1:4.
[0048] In the steps of the alumina modification method, step one is to remove impurities and soluble salts on the surface of alumina, improve the purity of the material, and facilitate subsequent modification and improvement of the performance of the composite material; step two is to remove moisture in alumina and further improve the purity through high-temperature treatment, while facilitating crystal transformation, improving the stability and crystallinity of the material, and creating suitable surface conditions for the subsequent adsorption of the coupling agent; step three is to uniformly coat the coupling agent on the surface of the alumina particles through wet stirring, and enhance the interfacial bonding force between alumina and the polymer matrix in the subsequent composite material; step four is to remove residual solvents in the material after the coupling agent treatment, promote the cross-linking and curing of the coupling agent molecules, and further enhance the modification effect.
[0049] The fluidity of polycarbonate is 1-30g / 10min.
[0050] Specific preparation method of high-toughness insulation and thermal conductive PC composite material:
[0051] 1. Alumina pretreatment: Use deionized water to repeatedly wash the alumina until the purity is ≥99.9%, then dry and calcine at high temperature to remove impurities and adjust the lattice structure;
[0052] 2. Silane coupling agent treatment: dilute the long-chain silane coupling agent (alkyl chain carbon number ≥ 8) in ethanol, mix in a mass ratio of 1:4, and use it to modify alumina and polycarbonate;
[0053] 3. Polycarbonate modification: Through high-speed mixing treatment, the long-chain silane coupling agent is fully contacted with the polycarbonate and heat-treated to form modified polycarbonate;
[0054] 4. Preparation of composite materials: After the treated alumina and modified polycarbonate are mixed with additives, high-mixing and high-temperature melting granulation technology is used to finally obtain high-toughness insulating and thermally conductive PC composite material particles.
[0055] Main technologies of high-toughness insulation and thermal conductive PC composite materials:
[0056] 1. Core component selection and design: 25% modified high-purity alumina is used as the basic skeleton to ensure the high insulation and good thermal stability of the material; alumina has various forms and its size is controlled within the range of 20-40000nm to optimize the internal structure of the material and promote heat conduction.
[0057] 2. Composite system construction: 65% silicone-modified polycarbonate not only enhances the processing fluidity and heat resistance of the material, but also achieves effective interface bonding through long-chain silane coupling agents, thereby improving the comprehensive performance of the material.
[0058] 3. Synergistic effect of additives: The 10% additive combination, especially the special treatment of thermal conductive filler and long-chain silane coupling agent, greatly improves the thermal conductivity and toughness of the material.
[0059] 4. Fine preparation process: Through strict alumina surface treatment, efficient application of silane coupling agent and precise control of ingredient ratio, combined with heat treatment steps at specific temperature, the uniform dispersion and performance optimization of the composite material are guaranteed.
[0060] By adding 12% toughening agent and other additives, the impact strength and toughness of the composite material are significantly enhanced, ensuring reliability and durability under high temperature or mechanical stress.
[0061] The use of long-chain silane coupling agent (alkyl chain carbon number ≥ 8) forms a strong chemical bond on the surface of alumina, optimizes the interfacial compatibility between inorganic fillers and organic matrices, and also improves thermal stability in polycarbonate modification, extending the service life of the material.
[0062] The fluidity of polycarbonate is controlled within the range of 1-30g / 10min. Combined with the efficient modification of the coupling agent, the material has excellent fluidity and is easy to form during processing, which facilitates large-scale production.
[0063] The addition of 2% coupling agent, 1% antioxidant and 25% flame retardant effectively improves the anti-aging ability, antioxidant and flame retardant properties of the composite material, ensuring the safe use of the material in complex environments.
[0064] Alumina has various forms (angular aluminum, spherical aluminum, flakes, whiskers) and a wide range of sizes (20-40000nm), which provides customized options for different application scenarios and enhances the flexibility of material design.
[0065] High-toughness insulation and thermal conductive PC composite materials achieve the following effects:
[0066] 1. Enhanced thermal conductivity: Fillers such as alumina, spherical magnesium oxide, boron nitride, and diamond powder have excellent thermal conductivity and can significantly improve the thermal conductivity of composite materials, which is crucial for applications that require efficient heat dissipation, such as electronic packaging materials, LED heat sinks, etc.
[0067] 2. Improved mechanical properties: The addition of toughening agents can increase the impact strength and toughness of the material, making the PC composite material more durable and less prone to cracking. The introduction of spherical magnesium oxide and diamond powder can also significantly enhance the mechanical strength and modulus of the material.
[0068] 3. Optimized processing performance: Silicone-modified PC can improve the fluidity and processability of the material, making it easier to shape the material during injection molding or extrusion, while reducing the internal stress of the product and improving the surface quality.
[0069] 4. Enhanced interfacial bonding: The role of the coupling agent is to enhance the interaction between the inorganic filler and the organic matrix, improve the overall performance of the composite material, and reduce the occurrence of delamination and cracks.
[0070] 5. Improved weather resistance and stability: The addition of antioxidants can effectively prevent the material from aging after long-term use or exposure to harsh environments, thereby extending its service life.
[0071] 6. Fire safety: The use of flame retardants can significantly improve the flame retardant properties of materials, ensure that the burning speed is reduced in the event of a fire, and reduce the release of toxic smoke. It is suitable for application scenarios with strict requirements on fire safety.
[0072] 7. Electromagnetic shielding effectiveness: Spherical magnesium oxide and diamond powder also have good electrical conductivity, which can provide a certain electromagnetic shielding effect for the composite material, and is suitable for applications that require electromagnetic compatibility, such as electronic equipment casings.
[0073] 8. Improved dielectric properties: The addition of zinc oxide can adjust the dielectric constant and loss factor of the material, which is beneficial for the production of high-frequency circuit boards and electrical components such as capacitors.
[0074] The present invention proposes a method for preparing a high-toughness insulating and thermally conductive PC composite material. Through a carefully designed formula and advanced preparation process, the material can significantly improve the thermal conductivity and mechanical toughness of the material while maintaining high insulation properties, meeting the stringent requirements for materials in high-tech fields such as electronic appliances, LED lighting, and communication equipment.
[0075] The composite material consists of 25% modified high-purity alumina, 65% organosilicon modified polycarbonate and 10% additives, wherein the additives include toughening agent, thermal conductive filler, coupling agent, antioxidant and flame retardant.
[0076] Alumina undergoes rigorous purification and surface modification treatments, uses a long-chain silane coupling agent, and undergoes two high-temperature calcinations to ensure excellent interfacial compatibility between alumina and the polycarbonate matrix; polycarbonate is also modified with the same coupling agent to enhance the material's toughness, heat resistance, and ability to bond with other components.
[0077] It effectively solves the contradictions in thermal conductivity, insulation, mechanical properties, etc. of traditional materials, and provides a new way to meet the demand for high-performance materials for electronic and electrical products.
[0078] Embodiment 1:
[0079] The composite material has a ratio of 25% modified high-purity alumina, 65% silicone-modified polycarbonate and 10% other additives, which are melt-compounded; the other additives are composed of a toughening agent, a thermal conductive filler, a coupling agent, an antioxidant and a flame retardant, and the ratio of the other additives is a mixture of 12% toughening agent, 60% thermal conductive filler, 2% coupling agent, 1% antioxidant and 25% flame retardant.
[0080] The thermal conductive filler is composed of cubic boron nitride, zinc oxide, spherical magnesium oxide and diamond powder. The proportion of the thermal conductive filler is: 45% cubic boron nitride, 40% zinc oxide, 7.5% spherical magnesium oxide and 7.5% diamond powder.
[0081] The following is an analysis of the effects of each component and its proportion on the performance of the composite material:
[0082] 1. Modified high purity alumina (25%):
[0083] Alumina is a good insulator with high hardness, high melting point and good chemical stability, which can improve the heat resistance and mechanical strength of composite materials. High purity helps to improve the electrical insulation performance and purity of the material.
[0084] 2. Silicone modified polycarbonate (65%):
[0085] The silicone modification gives the material better temperature resistance, weather resistance and electrical properties, while the carbonate matrix provides good transparency, chemical resistance and mechanical properties.
[0086] This matrix also has a low water absorption rate, which helps maintain the material's performance stability in humid environments.
[0087] 3. Other additives (10%):
[0088] 3.1. Toughening agent (12%): improves the toughness of the composite material and reduces the risk of brittle fracture.
[0089] 3.2. Thermal conductive filler (60%): It is composed of cubic boron nitride, zinc oxide, spherical magnesium oxide and diamond powder. Cubic boron nitride and diamond have extremely high thermal conductivity and can significantly improve the thermal conductivity of the material. Zinc oxide and spherical magnesium oxide can be used as auxiliary fillers to improve the uniformity and processability of the material.
[0090] 3.3. Coupling agent (2%): promotes the interface bonding between different components, enhances the interaction between filler and matrix, and improves the overall performance of the composite material.
[0091] 3.4. Antioxidant (1%): prevents materials from aging due to oxidation during processing and use, and prolongs service life.
[0092] 3.5. Flame retardant (25%): gives the material flame retardant properties and improves safety.
[0093] 4. Ratio of thermal conductive filler:
[0094] The high proportion of boron nitride and zinc oxide means that the composite material will have higher thermal conductivity and is suitable for application scenarios that require good heat dissipation, such as electrical appliances, electronics, and automobiles.
[0095] The addition of spherical magnesium oxide and diamond powder can not only further improve the thermal conductivity, but also improve the fluidity and filling properties of the composite material through its special shape.
[0096] Overall, the formula design takes into account the various properties of the material, including electrical insulation, thermal conductivity, mechanical strength, weather resistance, flame retardancy and processability, and is expected to produce an advanced composite material with high thermal conductivity, high insulation and high reliability that is suitable for high-end electronic device packaging, aerospace, automotive industry and other fields.
[0097] Embodiment 2:
[0098] The composite material has a ratio of 25% modified high-purity alumina, 65% silicone-modified polycarbonate and 10% other additives, which are melt-compounded; the other additives are composed of a toughening agent, a thermal conductive filler, a coupling agent, an antioxidant and a flame retardant, and the ratio of the other additives is a mixture of 12% toughening agent, 60% thermal conductive filler, 2% coupling agent, 1% antioxidant and 25% flame retardant.
[0099] The thermal conductive filler is composed of cubic boron nitride, zinc oxide, spherical magnesium oxide and diamond powder, and the proportion of the thermal conductive filler is a mixture of 35% cubic boron nitride, 30% zinc oxide, 10% hexagonal boron nitride and 10% mica powder.
[0100] The following is an analysis of the effects of each component and its proportion on the performance of the composite material:
[0101] 1. High toughness:
[0102] Toughening agent (12%): The main function of the toughening agent is to improve the toughness of the material, making the composite material less prone to brittle fracture when subjected to impact or stress, thereby improving the durability and service life of the material.
[0103] 2. Insulation:
[0104] Modified high-purity alumina (25%): High-purity alumina has excellent insulation properties, ensuring the reliability of the composite material in electrical applications.
[0105] 3: Thermal conductivity
[0106] 3.1. Thermal conductive filler (60%), including 35% cubic boron nitride, 30% zinc oxide, 10% hexagonal boron nitride and 10% mica powder.
[0107] 3.2. Cubic boron nitride (BN) and hexagonal boron nitride (h-BN) are both materials with high thermal conductivity, which can effectively improve the thermal conductivity of composite materials and facilitate the rapid conduction of heat energy.
[0108] 3.3. Although zinc oxide (ZnO) has a slightly lower thermal conductivity, it can increase the density of the heat conduction network as a supplementary filler and further improve the overall thermal conductivity.
[0109] 3.4. The addition of mica powder helps to improve the thermal stability of the material. It can also serve as an auxiliary filler for heat conduction and improve the uniformity and processing performance of the composite material.
[0110] 4. Processability and chemical stability
[0111] Silicone modified polycarbonate (65%): Silicone modification not only improves the temperature resistance and weather resistance of the material, but also enhances the processability of the composite material, making it easier to shape and process.
[0112] 5. Anti-aging and flame retardancy
[0113] 5.1. Antioxidant (1%): Antioxidant can prevent the material from aging due to oxidation during use and extend the service life of the material.
[0114] 5.2 Flame retardant (25%): Although the proportion in "other additives" seems too high, considering that this is the proportion within "other additives", it actually accounts for a smaller proportion of the entire composite material. The addition of flame retardants can improve the safety of the material and make it meet the flame retardant standards of specific applications.
[0115] This composite material achieves high toughness, good insulation and excellent thermal conductivity, while also taking into account processability, chemical stability and flame retardancy.
[0116] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.
Claims
1. A high-toughness insulating and thermally conductive PC composite material, characterized in that: The composite material is formed by melt compounding of modified high-purity alumina, silicone-modified polycarbonate and other additives; The composite material is prepared by melting and compounding the modified high-purity alumina at a ratio of 25%, the organic silicon modified polycarbonate at a ratio of 65% and other additives at a ratio of 10%.
2. The high-toughness insulating and thermally conductive PC composite material according to claim 1, characterized in that: The aluminum oxide may be angular aluminum, quasi-spherical aluminum, flaky aluminum oxide, or aluminum oxide whiskers. The size of the aluminum oxide is 20-40000 nm.
3. The high-toughness insulating and thermally conductive PC composite material according to claim 1, characterized in that: The other additives are composed of toughening agent, thermal conductive filler, coupling agent, antioxidant and flame retardant, and the proportion of the other additives is: toughening agent 12%, thermal conductive filler 60%, coupling agent 2%, antioxidant 1% and flame retardant 25%.
4. The high-toughness insulating and thermally conductive PC composite material according to claim 3, characterized in that: The thermally conductive filler is a mixture of at least two thermally conductive materials.
5. The method for preparing a high-toughness insulating and thermally conductive PC composite material according to claim 2, characterized in that: The method for preparing the composite material comprises the following steps: Step 1: High-purity alumina is repeatedly washed with water to a purity of more than 99.9%; Step 2: using a long-chain silane coupling agent for surface treatment and performing two high-temperature calcination treatments; Step 3: silicone-modified polycarbonate: a long-chain silane coupling agent is selected and mixed with polycarbonate powder at high speed, and after the surface of the polycarbonate is completely wetted, heat treatment is performed at 120° C. for 2 hours to obtain a long-chain silane-modified polycarbonate; Step 4: Mix the treated modified high-purity alumina, silicone-modified polycarbonate and other additives, and then perform high-temperature melt granulation to obtain a high-toughness insulating and thermally conductive polycarbonate composite material.
6. The long-chain silane coupling agent in the method for preparing a high-toughness insulating and thermally conductive PC composite material according to claim 4, characterized in that: The number of carbon atoms in the alkyl chain is ≥8.
7. The alumina modification method in the high-toughness insulating and thermally conductive PC composite material and its preparation method according to claim 4, characterized in that: Alumina modification method steps: Step 1: Alumina is repeatedly washed with deionized water until the purity of the alumina is ≥ 99.9%; Step 2: Dry at 120 degrees for 2 hours, then heat to 800 degrees, calcine for 2 hours, and finally slowly heat to 1500 degrees and keep the temperature constant for 2 hours; Step 3: dilute the long-chain silane coupling agent in ethanol, and add 1000g of alumina to 100g of the long-chain silane coupling agent; Step 4: wet stirring for half an hour, and then drying at 150°C for 4 hours.
8. The method for preparing a long-chain silicone coupling agent modified polycarbonate in the method for preparing a high-toughness insulating and thermally conductive PC composite material according to claim 4, characterized in that: The coupling agent is diluted in ethanol at a mass ratio of 1:
4.
9. The polycarbonate in the method for preparing a high-toughness insulating and thermally conductive PC composite material according to claim 4, characterized in that: The polycarbonate has a fluidity of 1-30 g / 10 min.